2015
DOI: 10.1017/s2040174415001506
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of antibiotic resistance genes in infants’ meconium and early fecal samples

Abstract: The gastrointestinal tract (GIT) microbiota has been identified as an important reservoir of antibiotic resistance genes (ARGs) that can be horizontally transferred to pathogenic species. Maternal GIT microbes can be transmitted to the offspring, and recent work indicates that such transfer starts before birth. We have used culture-independent genetic screenings to explore whether ARGs are already present in the meconium accumulated in the GIT during fetal life and in feces of 1-week-old infants. We have analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 58 publications
5
63
0
Order By: Relevance
“…Maternal antibiotic exposure was associated with expression of carbapenem-hydrolyzing enzymes of the Vim -1 gene in 6 of 23 neonates that received antibiotics. Previous studies have also reported the presence of Vim -type genes in infants4950. Carbapenem-resistant isolates of Pseudomonas aeruginosa and other gram-negative non-fermenters have been identified to be Vim -1-containing microorganisms51.…”
Section: Discussionmentioning
confidence: 79%
“…Maternal antibiotic exposure was associated with expression of carbapenem-hydrolyzing enzymes of the Vim -1 gene in 6 of 23 neonates that received antibiotics. Previous studies have also reported the presence of Vim -type genes in infants4950. Carbapenem-resistant isolates of Pseudomonas aeruginosa and other gram-negative non-fermenters have been identified to be Vim -1-containing microorganisms51.…”
Section: Discussionmentioning
confidence: 79%
“…Given the potential role of the gut microbiota as reservoir for antibiotic resistance genes, the early microbiota establishment may also constitute a critical step from this perspective. Some studies have reported the presence of antibiotic resistance genes in the early life microbiota [49, 50]. Gosalbes and co-workers [50] demonstrated the presence of genes conferring resistance to β-lactam antibiotics and tetracycline in the meconium of more than half of the newborns.…”
Section: Discussionmentioning
confidence: 99%
“…This microbial profile strongly resembles that of young infants, but importantly is significantly influenced by a range of maternal factors. For example, maternal eczema has been linked to newborn respiratory disorders (51). Therefore, there is a necessary overlap of the maternal immune system with that of the fetus and this extends beyond the direct innate maternal mechanisms that were previously assumed to be the only operative ones.…”
Section: Variations Within the Human Microbiomementioning
confidence: 99%
“…It also becomes clear that the development of that “organ” is a function of a significant overlap with the maternal microbiome. For example, Gosalbes et al used culture-independent genetic screening to demonstrate a high incidence of maternally transferred antibiotic-resistant genes in infant’s meconium and fecal samples, at least some of which is presumed to have occurred in utero (51). …”
Section: The Impact Of the Microbiome On Developmentmentioning
confidence: 99%